The impact of voluntary audit on credit ratings: evidence from UK private firms - Dedman, Elisabeth (2013)
After a long period of universal mandatory audit, the UK reduced the regulatory burden of private ﬁrms by introducing size-based audit exemption in 1994; the size thresholds have subsequently been progressively increased. Both accounting bodies and credit-rating agencies (CRAs) have expressed reservations about this policy, arguing it could diminish user conﬁdence in reported accounting numbers, and lead to a reduction in ﬁnancial statement quality and credit ratings. Prior research, however, suggests that the managers of small UK companies do not perceive there to be an association between ﬁnancial statement audit and ﬁrm credit score. To provide evidence of any effect on user conﬁdence of making audit optional, we examine the credit scores and ﬁnancial reporting quality of a large sample of UK private ﬁrms which qualiﬁed for audit exemption after major threshold changes in 2004. We ﬁnd that, even though they report lower average proﬁts, companies which retain a voluntary audit enjoy signiﬁcantly higher credit scores than those which opt out of audit. The results of both conservatism and accruals-based tests indicate that opting out of audit is associated with less conservative ﬁnancial reporting, consistent with the concerns of the accounting bodies and the CRAs, and providing an explanation for why opt-out ﬁrms report higher proﬁts but receive lower credit scores. This study contributes to an important policy debate by providing large sample evidence that the audit does confer beneﬁts to private ﬁrms in terms of ﬁnancial reporting quality, assurance and the credit scores generated from the ﬁnancial reports.